A collaborative system for endovascular treatment of acute ischaemic stroke: the Madrid Stroke Network experience. (13th June 2015) - Alonso de Leciñana, M.; Fuentes, B.; Ximénez‐Carrillo, Á.; Vivancos, J.; Masjuan, J.; Gil‐Nuñez, A.; Martínez‐Sánchez, P.; Zapata‐Wainberg, G.; Cruz‐Culebras, A.; García‐Pastor, A.; Díaz‐Otero, F.; Fandiño, E.; et al.
Abstract : Background and purpose: The complexity and expense of endovascular treatment (EVT) for acute ischaemic stroke (AIS) can present difficulties in bringing this approach closer to the patients. A collaborative node was implemented involving three stroke centres (SCs) within the Madrid Stroke Network to provide round‐the‐clock access to EVT for AIS. Methods: A weekly schedule was established to ensure that at least one SC was 'on‐call' to provide EVT for all those with moderate to severe AIS due to large vessel occlusion, >4.5 h from symptom onset, or within this time‐window but with contraindication to, or failure of, systemic thrombolysis. The time‐window for treatment was 8 h for anterior circulation stroke and <24 h in posterior stroke. Outcomes measured were re‐canalization rates, modified Rankin Scale (mRS) score at 3 months, mortality and symptomatic intra‐cranial haemorrhage (SICH). Results: Over a 2‐year period (2012–2013), 303 candidate patients with AIS were considered for EVT as per protocol, and 196 (65%) received treatment. Reasons for non‐treatment were significant improvement (14%), spontaneous re‐canalization (26%), clinical worsening (9%) or radiological criteria of established infarction (31%). Re‐canalization rate amongst treated patients was 80%. Median delay from symptom onset to re‐canalization was 323 min (p25; p75 percentiles 255; 430). Mortality was 11%; independence (mRS 0–2) was 58%; SICH was 3%. Conclusions: Implementation of a collaborative network to provide EVT for AIS is feasible and effective. Results are good in terms of re‐canalization rates and clinical outcomes. Abstract : Clickhere to view the accompanying paper in this issue.